SOCIO-PHILOSOPHICAL FEATURES OF ENHANCING THE INFORMATION CULTURE OF YOUTH IN MODERN CONDITIONS - Abrayev Sherzod (Scholar Express Journal, 2025)
This article analyzes the need to form and enhance the information culture of young people in a context where globalization is developing at a new stage worldwide with the emergence and growth of a rapidly expanding information space. The article also highlights that, under such conditions, the rapid penetration of modern information technologies into all spheres, the development of an open information system, and the necessity of improving the culture of information consumption in society have become evident
Keywords: Information; information space; open information; information culture